2015
DOI: 10.3109/19396368.2015.1069420
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for clock genes circadian rhythms in human full-term placenta

Abstract: Biological rhythms are driven by endogenous biological clocks; in mammals, the master clock is located in the suprachiasmatic nucleus (SCN) of the hypothalamus. This master pacemaker can synchronize other peripheral oscillators in several tissues such as some involved in endocrine or reproductive functions. The presence of an endogenous placental clock has received little attention. In fact, there are no studies in human full-term placentas. To test the existence of an endogenous pacemaker in this tissue we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 39 publications
1
29
1
Order By: Relevance
“…Remarkably, and unlike mouse pregnancy, we did not detect any oscillation patterns in clock genes in term human placentas, which is not consistent with previous studies of placentas from vaginal deliveries ( 42 ). This discrepancy may be because we used placentas from elective cesarean sections.…”
Section: Discussioncontrasting
confidence: 99%
“…Remarkably, and unlike mouse pregnancy, we did not detect any oscillation patterns in clock genes in term human placentas, which is not consistent with previous studies of placentas from vaginal deliveries ( 42 ). This discrepancy may be because we used placentas from elective cesarean sections.…”
Section: Discussioncontrasting
confidence: 99%
“…This "master clock" relies on the functional role of the core clock proteins, Clock and Bmal1, which enables clock gene expression. As mentioned before, these circadian clock genes are all expressed in animal and human placenta, and their expression shows a potential circadian rhythm [26,57]. Several studies have shown the crucial role that the circadian clock and SCN play in female reproductive function [21,22,58].…”
Section: Embryonic Brain Scnmentioning
confidence: 84%
“…It should be noted, however, that external effects cannot be ruled out, such as the stress of vaginal delivery, including the increase in stress hormones known to affect gene expression. Only two of the genes studied-Clock and Bmal1, showed any circadian variation [26].…”
Section: Future Directions and Perspectivesmentioning
confidence: 92%
See 1 more Smart Citation
“…Besides, other organs (e.g., placenta) may play a direct role. Full-term placenta expresses circadian rhythms of Clock and Bmal1 ( 72 ), and clock gene polymorphisms are associated with placental abruption ( 73 ) and even a single polymorphism of Bmal1 is associated with an increase in miscarriages ( 27 ). Finally, RNA microarray analysis of human milk fat globules indicates differential daily expression of 7% of transcripts ( 74 ).…”
Section: Translational Importance Of Circadian Rhythms and Clock Genementioning
confidence: 99%